(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2024)
Purpose: One of the crucial steps towards fully grasping the benefits of smartphone use for all is to explore the existence of a digital divide and its relationship to different outcomes of smartphone use. In so doing, this study explored the smartphone-related digital divide among South Korean older adults in terms of access, use and outcomes. Design/methodology/approach: In-person interviews using questionnaires were conducted to collect the data from a total number of 372 older adults aged 60 and above in eleven community centers in the Seoul Metropolitan area in Korea, 223 of whom owned a smartphone. Results: This study found that most participants use smartphones to communicate with personal relationships and support system. There were, however, differences among groups related to gender, age, and ICT training in terms of the extent of smartphone usage and participation in virtual communities. In three age groups of 60+, 70+ and 80+, a younger cohort and those with ICT training had higher smartphone literacy, harnessing the potential of smartphones. Those who used smartphones to stay connected to their social group and for entertainment showed a lower level of loneliness. Conclusion: This study shows that older adults (i.e., 60+) are not a homogenous group when it comes to using smartphones. There are distinct differences in older smartphone users, especially in the age groups 60+, 70+ and 80+. Older adults should be encouraged to use smartphones for better connectivity with their social groups and entertainment, potentially decreasing their feeling of loneliness.